Brassica tournefortii Gouan (Brassicaceae), nuevo registro para la flora alóctona asilvestrada de Chile - TEILLIER, SEBASTIÁN; PRINA, ANÍBAL; LUND, ROSEMARIE (Gayana Botánica, 2014)
Brassica tournefortii is registered for first time for Chilean territory as an alien plant species. A brief description and illustrations are given. The specimens here cited were collected in Los Molles (32°14’S-71°31’W) at Valparaiso Region at the Pacific coast of Chile.